Optimization of conditions for in vitro micrografting in rubber (Hevea brasiliensis) - Kala R G; Asokan M P; Jayashree R; Jayasree K P; Rekha K; Sobha S; Thulaseedharan A (Indian Journal of Natural Rubber Research, 2002)
The conditions for successful in vitro micrografting such as the nature of cut and type of support, age and size of stock and scion, the physical nature of the medium and effect of antioxidants were standardised for Hevea brasiliensis. The micrografting was carried out using zygotic embryo derived plantlets raised in vitro. Ex vitro micrografting was standardised using polybag grown seedlings as root stocks and scions from glass house grown plants. Maximum success rate was obtained with saddle type of cut with parafilm as the support. Thirty day-old stocks and 21 day-old scions had considerably enhanced the success rate. Scions of length 1.5 cm were ideal for micrografting. Maximum success rate was observed when 60 g/1 sucrose was included in the culture medium. Application of the antioxidant ascorbic acis, at a concentration of 100mg/1 to the cut surface of the explants, prevented browning as well as in increased the survival rate. The technique is useful for combining genetically and physiologically comparable rootstocks and scion of elite clones produced by genetic engineering.
Keywords: Hevea brasiliensis; In vitro micrografting; Micropropagation; Zygotic embryos